Evaluation of semen characteristics of the species Mazama americana in captivity - Rola, Luciana Diniz [UNESP]; Zanetti, Eveline Dos Santos [UNESP]; Duarte, José Maurício Barbanti [UNESP] (CSIRO Publishing, 2013)
In recent years the concept of genomic resource banks has grown as a way of maintaining the genetic variability of populations, while the quality of cryopreservation of the gametes determines the effectiveness of such banks. However, the absence of basic knowledge regarding the physiology of species and their semen characteristics hampers the establishment of reproductive biotechnologies. Thus, this paper aimed to determine certain physicochemical (volume, colour, appearance, pH and osmolarity) and microscopic characteristics (mass movement, motility, vigour, concentration, and sperm morphology and morphometry) of semen of the species Mazama americana. To achieve this, five males of the species were used, and three semen samples per buck (electroejaculation) were collected at intervals of 2 weeks. The volume, pH and osmolarity of the ejaculate were 0.39 ± 0.14 mL, 6.90 ± 0.74 and 297.74 ± 19.10 mOsm/kg, respectively, while the values obtained for mass movement, motility, vigour and concentration were 3.33 ± 0.82; 69.6 ± 8.92%; 3.53 ± 0.50, and 244.07 ± 98.65 × 107/mL, respectively. Regarding the colour of the ejaculate, five samples were classified as ivory, two as yellowish, two as whitish and six as white. Regarding appearance, seven samples were considered creamy and eight, milky. Morphology was analysed in a humid chamber under phase contrast microscopy and 73.50 ± 5.57% of cells presented normal morphology, 8.37 ± 3.15% presented major defects and 18.13 ± 6.46% presented minor defects. To determine sperm morphometry, an optical microscope (Leica DM 5000B) and the Leica Qwin image analyser program were used, resulting in 8.09 ± 0.40, 4.65 ± 0.30, 2.81 ± 0.44 and 30.25 ± 3.02 m for length, largest width, smallest width and area, respectively. Copyright © CSIRO 2013.
Keywords: Cervids; Electroejaculation; Genomic banks; Red brocket deer; biotechnology; body fluid; captivity; concentration (composition); cryopreservation; deer; genetic resource; genetic variation; genomics; morphology; morphometry; motility; movement; pH; physicochemical property; sperm; vigor